A perspectiva dos professores da educação a distância frente ao ensino de pessoas com deficiência - Silva, Naiara Nunes da (2022)
Distance education has been gaining prominence and being increasingly recognized, especially due to the technological advances that have taken place in recent years. As it is a trend in the field of education, the present study sought to analyze the perception of distance education teachers regarding the teaching of people with disabilities. In order to do so, we answer the following research problem: How do distance education teachers act when teaching people with disabilities in higher education? With this in mind, this research has as its general objective: to investigate, from the point of view of distance education teachers, the challenges faced in teaching people with disabilities and as specific objectives: to investigate what are the biggest challenges faced by teachers, what are the skills necessary for them to teach people with disabilities in the distance modality and what are the main solutions proposed by them to face the challenges mentioned. The theoretical discussion was based on legal regulations, as well as by several authors who talk about Distance Education and the teaching of People with Disabilities, among others. For its development, we used a qualitative approach as a methodology and bibliographic and exploratory research were adopted as methodological procedures. Data collection and generation were carried out through field research, with interviews with teachers who work in Distance Education. For data analysis, the assumptions of content analysis, proposed by Bardin (2016), were used. The results obtained raise important points about the difficulties encountered by teachers, such as: a) identification of students with disabilities; b) promotion of egalitarian education; c) reliability in the results; d) prejudice and d) fear of dealing with specific disabilities that they find challenging. In addition, they identify that there are skills necessary for teaching PwD: a) affectivity and b) communication; in addition to the need for continuing education for teachers. Finally, they point out solutions to the problems, such as: a) use of specific methodologies for each disability and b) identification of students with disabilities at the beginning of the semester. In addition, some professors highlighted personal practices that they consider successful.